The influence of shipping and online consumer reviews on purchase decisions on Shopee e-commerce among economics education students at Nusa Cendana University - Keluanan, Juananda; Abolladaka, Jacob; Saragih, Fernando (Privietlab, 2026)
In the current digital era, the Internet has provided convenience for many parties to market products through online media. However, several factors continue to influence consumers’ choices when shopping online. Therefore, this study focuses on examining consumer behavior in making purchases, considering consumer reviews and free shipping. The objective of this study was to understand how each element affects purchasing decisions in the Shopee online marketplace, both partially and simultaneously. The approach used was survey-based and quantitative. The population of this study comprised all 485 students of the Economics Education program at Undana, with a sample of 220 respondents determined through probability sampling using a simple random sampling technique based on Slovin’s formula. A questionnaire containing 24 statements that had undergone validity and reliability tests was used as the research instrument. With the assistance of SPSS version 27, the data analysis was conducted using multiple linear regression, complemented by t-tests, F-tests, and the coefficient of determination. The findings indicate that online consumer reviews and free shipping have a positive and significant impact on consumers’ purchasing decisions. With an F-value of 169.693 and a significance level of 0.000, these two factors also have a significant combined effect. The results show that these elements significantly influence the purchasing decisions of Economics Education students at Universitas Nusa Cendana on Shopee e-commerce platforms.